Spatial dynamics of lepidopterous pests on Zea mays (Linnaeus) and Pennisetum purpureum (Moench) in the forest zone of Cameroon and their implications for sampling schemes - Ndemah, R.; Poehling, H.; Borgemeister, C.; Schulthess, F. (2001)
common lepidopterous borers attacking maize and/or the wild host Penni.l'etum purpureum in the forest zonc of Camcroon arc the noctuids Buss('ola.li/sca (Fuller), Sesamia calamistis (Hampson) and Poeol1oma serrata (Hampson), the pyralids Eldani! s{{cc/wrin{{ (Walker) and Mus.l'idia nigrivel1ella (Ragonot), and Cryptophlehia leucotreta (Tortricidae). The within-plant distribution on maize and elephant grass was studied for the predominant species B . .Iil.\·('(l, and on maize only for E. s{{ccharilla to determine the basic sampling unit. On both plant species, B . .Ii/sea showed a strong oviposition preference for young plant parts. By contrast, E. .I'acc/wrina larvae and pupae on maize were only found on older plant parts indicating that it does not oviposit on young plants. No part of the plant strata appeared to be a stable sampling unit and it is recommended to carry out whole plant or whole tiller sampling for maize and grass, respectively. For the development of sampling plans, dispersion was described for all species using Taylor's power law and a non-linear model which gives the relationship between the proportion of infested plants [P(J)] and mean density (/11). Busseo/{{ fi/sca egg batches as well as diapausing larvae and pupae on maize showed a random distribution whereas all the other cases were aggregated, with B. fu.l'c([ egg batches on elephant grass exhibiting the lowest and M. lligriv(,I1('lIa on maize the highest aggregation. Optimal sample size/mean density curves were developed for groups of insects with low and high aggregation.